Combinatorial effect of plant-honeys on preventing the gou desease - Yabrir, Ilyes Mohamed El Amine; Djeridane, Amar; Hamia, Chahrazed (Laghouat : Université Amar Telidji - Département des sciences de la matière, 2025)
This laboratory study aimed to evaluate the effectiveness of 12 extracts issued of binary combination of two medicinal plants and six local honeys as inhibitors of xanthine oxidase, protein hydrolysis, and uric acid dissolution. It also evaluated their effect on red blood cells, as well as examined some phytochemical compounds. The analysis showed that there were monumental differences in the content of phenolic compounds and mineral salts according to the plant and honey species. The experiments revealed that all the extracts possessed varying degrees of anti-gout action. The best was Laurus nobilis and Rosmarinus officinalis (two honeys). They presented the strongest inhibition of xanthine oxidase and highest ability to dissolve uric acid. However, it has been noted that Laurus nobilis extract is harmful to red blood cells, as compared to Rosmarinus officinalis, thus making it a safer molecule for the therapeutic treatment of diseases caused by this enzyme.
an in vitro study